Enhancement of Optical Properties and Stability in CsPbBr3 Using CQD and TOP Doping for Solar Cell Applications - Chiayee Salih Ajaj; Diyar Sadiq (Journal of Nanotechnology)
Cesium lead bromide (CsPbBr3) nanocrystals exhibit remarkable optoelectronic properties and exceptional stability. As a result, they have garnered significant interest for their potential applications in various fields, including solar cells, light-emitting devices, photodetectors, and lasers. Despite its resistance to moisture, oxygen, and heat compared to other perovskite materials, CsPbBr3 still faces challenges maintaining its structural and optical stability over extended periods. This study proposes a robust solution to enhance and improve simultaneously the photoluminescence intensity and stability of CsPbBr3 nanocrystals. The solution involves doping the perovskite precursor with green-synthesized carbon quantum dots (CQDs) and tri-n-octyl phosphine (TOP). The results indicate that the photoluminescence intensity of the perovskite nanocrystals (NCs) is sensitive to varying CQD ratios. A high photoluminescence intensity enhancement of 45% was achieved at the optimal CQDs ratio. The synthesized perovskite NCs/CQDs also demonstrated improved stability by adding TOP into the mixture. After storage in the air for 45 days, the mixed perovskite NCs maintained their performance, which was almost unchanged. Solar cell devices based on the modified perovskite NCs showed a power conversion of 7.74%. The devices also demonstrated a significant open-circuit voltage (VOC), with the most successful device achieving a VOC of 1.193 V, an Isc of 10.5748 mA cm−2, and a fill factor (FF) of 61%. This study introduces a cost-effective method for producing high-quality all-inorganic optoelectronic devices with enhanced performance and stability.